Evaluasi Program Strategis Nasional dalam Meningkatkan Kesejahteraan Masyarakat terhadap Jam Operasional Truk Tanah - Suci Dwi Mareta; Finnatun Finnatun; Khikmawanto Khikmawanto (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
Program strategis nasional (PSN) in Indonesia public welfare through social, economic,environmental, and governance dimensions. Findings indicate that limiting truck operations during peak hours generally contributes to reduced traffic congestion, improved road safety, and lower levels of pollution and noise in residential areas. However, the effectiveness is constrained by weak enforcement, frequent rule violations by operators, and limited crosssector coordination. To enhance the policy's positive impact, this study recommends strengthening law enforcement, utilizing monitoring technologies, and developing a more integrated and participatory logistics system. When consistently and collaboratively implemented, the policy has significant potential to support the success of NSPs and improve community welfare.